2005
DOI: 10.1641/0006-3568(2005)055[0583:eohfpp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Hormone Function: Proglucagon-derived Peptides and Their Receptors

Abstract: The mammalian proglucagon gene encodes three related sequences, glucagon and the glucagon-like peptides 1 and 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 54 publications
(109 reference statements)
1
28
0
1
Order By: Relevance
“…This conclusion was drawn from an analysis of a more complete set of receptor genes from diverse vertebrate species and was strengthened by the claim that the putative fish Glp1r was in a genomic neighbourhood that was conserved with amphibians and was linked to genes that are on the same chromosome that encodes mouse Glp1r [28]. In contrast to our earlier analysis [17,35], this new study [28] only identified four genes, instead of the five we detected, in the Xenopus genome with similarity to the mammalian receptors for proglucagon‐derived peptides and GIP. These observations prompted us to conduct a new phylogenetic and genomic analysis of diverse vertebrate genomes for genes similar to mammalian Gcgr , Glp1r , Glp2r and Gipr .…”
Section: Glucagon Receptor Gene Subfamilymentioning
confidence: 66%
See 1 more Smart Citation
“…This conclusion was drawn from an analysis of a more complete set of receptor genes from diverse vertebrate species and was strengthened by the claim that the putative fish Glp1r was in a genomic neighbourhood that was conserved with amphibians and was linked to genes that are on the same chromosome that encodes mouse Glp1r [28]. In contrast to our earlier analysis [17,35], this new study [28] only identified four genes, instead of the five we detected, in the Xenopus genome with similarity to the mammalian receptors for proglucagon‐derived peptides and GIP. These observations prompted us to conduct a new phylogenetic and genomic analysis of diverse vertebrate genomes for genes similar to mammalian Gcgr , Glp1r , Glp2r and Gipr .…”
Section: Glucagon Receptor Gene Subfamilymentioning
confidence: 66%
“…While a Glp1r gene was not identified in fish genomes, orthologs of Gcgr , Glp2r and Gipr were [17,35,36]. In our initial analysis [17,35] the putative Gipr group was poorly supported and did not reflect the accepted species phylogeny. Additionally, in some analyses it was suggested that there were two different types of receptors in this group.…”
Section: Glucagon Receptor Gene Subfamilymentioning
confidence: 76%
“…Studies have revealed that intimate interacting partners do not always emerge simultaneously; specific interactions among biomolecules often form in a stepwise Darwinian fashion, as parts of systems do not remain static and can be co-opted for novel functions (Thornton 2001, Irwin 2005, Bridgham et al 2006, J He, D M Irwin, Y P Zhang, unpublished observations). Gene duplication, and gain and loss of interactions through mutations in existing proteins are the two recognized major evolutionary processes shaping the specific interactions among biomolecules (Wagner 2001, 2003, Berg et al 2004.…”
Section: Introductionmentioning
confidence: 98%
“…Because there is an intimate association between the ligand and receptor, one might expect that the genes for receptors and hormones should co-evolve, and that new ligandreceptor pairs would evolve from parallel duplications of the hormone and receptor genes [35,36]. However, the evolutionary history of MLNR does not match that of its cognate ligands.…”
Section: Discussionmentioning
confidence: 99%